PENGELOLAAN PROGRAM DIGITALISASI PADA SEKOLAH PENGGERAK (Studi Multi Situs di SDN 73 Sudu dan SDN 132 Malele Kabupaten Enrekang) - Mardiana; Ansar; Muhammad Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the management of digitalization programs in "Sekolah Penggerak" (Driving Schools). The purpose of this research is to explore how digitalization program management is conducted at SDN 73 Sudu and SDN 132 Malele, focusing on planning, implementation, and supervision, as well as identifying the supporting and inhibiting factors in managing digitalization programs. The research method used is qualitative, with data collected through interviews, observations, and documentation. Data analysis was carried out in four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the planning of digitalization programs in "Sekolah Penggerak" at SDN 73 Sudu and SDN 132 Malele highlights the importance of a systematic approach to implementing digital transformation in educational settings. Several key aspects of digitalization planning were identified, including needs assessment, vision and mission formulation, teacher involvement in planning, budget allocation, and the principal’s role. In terms of program implementation, the utilization of various digital platforms such as the Merdeka Mengajar Platform (PMM), Educational Report, and ARKAS is supported by key integrated aspects, including teacher training and mentoring, adequate digital infrastructure, and collaboration among teachers through active and dynamic learning communities. Furthermore, the supervision aspect demonstrates a comprehensive approach encompassing technical, pedagogical, and managerial aspects. The supporting and inhibiting factors influencing the implementation of digitalization programs at SDN 73 Sudu and SDN 132 Malele include infrastructure, human resources, budget, policy, curriculum, and stakeholder support.